2021
DOI: 10.3390/life11050451
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation Induces Resistant Glioblastoma Stem-Like Cells by Promoting Autophagy via the Wnt/β-Catenin Pathway

Abstract: Therapeutic resistance in recurrent glioblastoma multiforme (GBM) after concurrent chemoradiotherapy (CCRT) is a challenging issue. Although standard fractionated radiation is essential to treat GBM, it has led to local recurrence along with therapy-resistant cells in the ionizing radiation (IR) field. Lines of evidence showed cancer stem cells (CSCs) play a vital role in therapy resistance in many cancer types, including GBM. However, the molecular mechanism is poorly understood. Here, we proposed that autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…However, our work did not focus on intercellular Ca 2+ in autophagy or the associated signaling pathways. An abundance of data indicates that the PI3K/Akt/mTOR, ERK1/2 and β-catenin signaling pathways are closely related to proliferation, apoptosis and autophagy [70] , [71] , [72] . In addition, extensive studies have reported that accumulating ROS inhibits the PI3K/Akt/mTOR, ERK1/2 and β-catenin pathways, leading to autophagy and apoptosis [36] , [37] , [73] .…”
Section: Discussionmentioning
confidence: 99%
“…However, our work did not focus on intercellular Ca 2+ in autophagy or the associated signaling pathways. An abundance of data indicates that the PI3K/Akt/mTOR, ERK1/2 and β-catenin signaling pathways are closely related to proliferation, apoptosis and autophagy [70] , [71] , [72] . In addition, extensive studies have reported that accumulating ROS inhibits the PI3K/Akt/mTOR, ERK1/2 and β-catenin pathways, leading to autophagy and apoptosis [36] , [37] , [73] .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we aimed to explore the underlying mechanism that regulates CD44 expression in GBM cells after irradiation treatment. Previously, it was reported that fractionated IR could induce GSCs with the stemness phenotype by P62-mediated autophagy through the Wnt/β-catenin axis [ 38 , 39 ]. In our research, based on our previous study [ 12 ], we found that irradiated GBM cells can upregulate CD44 expression to induce stemness features.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanations were as follows: AKIP1 regulated some key oncogenetic pathways, such as Wnt/β-catenin, PI3K/AKT, Notch pathways, etc. These pathways are closely engaged in regulating cancer stemness in GBM [25] , [26] , [27] .…”
Section: Discussionmentioning
confidence: 99%